2016
DOI: 10.1097/iop.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Features of Nasolacrimal Silastic Stents Retained for Prolong Durations Following Dacryocystorhinostomy

Abstract: This is the first study to exclusively report on scanning electron microscopic features of lacrimal stents retained for long durations. Further studies on physical elements within the deposits and protein analysis would provide more insights into stent-tissue interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…16 For Crawford stents retained for greater than 1 year in patients lost to follow-up after DCR, biofilms were also noted to be more extensive with greater stent retention time. 17 However, in both of these studies, none of the patients showed clinical signs or symptoms of infection, and the clinical implications of the observed biofilms are not well understood. 16,17 The Lacriflow tube is made of a different polymer than Monoka and Crawford stents, which could hold different properties in relation to biofilm formation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…16 For Crawford stents retained for greater than 1 year in patients lost to follow-up after DCR, biofilms were also noted to be more extensive with greater stent retention time. 17 However, in both of these studies, none of the patients showed clinical signs or symptoms of infection, and the clinical implications of the observed biofilms are not well understood. 16,17 The Lacriflow tube is made of a different polymer than Monoka and Crawford stents, which could hold different properties in relation to biofilm formation.…”
Section: Discussionmentioning
confidence: 96%
“…17 However, in both of these studies, none of the patients showed clinical signs or symptoms of infection, and the clinical implications of the observed biofilms are not well understood. 16,17 The Lacriflow tube is made of a different polymer than Monoka and Crawford stents, which could hold different properties in relation to biofilm formation. 6 Future studies are indicated comparing Lacriflow stents to other bicanalicular systems in the rates of clinically evident colonization as well as biofilm formation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Авторы вышеописанной методики проводят антифибротическую профилактику только в тканях полости носа, не воздействуя при этом на ткани слезного мешка. Кроме того, в конце операции они интубируют дакриостому силиконовым имплантатом, что сопряжено не только с нежелательной продолжительной его ретенцией, но и с возможным развитием ряда осложнений, в частности с образованием грануляций и инфицированием (в том числе устойчивыми возбудителями, ассоциированными с биопленками [27]), что может привести к рецидиву дакриоцистита [28].…”
Section: Discussionunclassified
“…The same group recently published scanning electron microscopic imaging data demonstrating the presence of biofilm on silastic stents after routine and prolonged duration stent removal following DCR. 11,12 Questions remain regarding the primary pathogens responsible for infection, whether organisms growing on clinically infected lacrimal stents are the same as those found in normal nasolacrimal flora, and the role of biofilm in pathogenesis.…”
mentioning
confidence: 99%